1999
DOI: 10.1080/000155599750010706
|View full text |Cite
|
Sign up to set email alerts
|

Patch-test Reactions to Plastic and Glue Allergens

Abstract: Plastics and glues are common causes of occupational dermatoses, but only few reports have dealt with patch-test reactions caused by plastic and glue allergens. Patients exposed to plastics and remitted to an occupational dermatology clinic, were patch-tested with 50-53 plastic and glue allergens during a 6-year period. Conventional patch-test techniques were used. The most common causes of allergic patch-test reactions in 360 patients were novolac epoxy resin (5.1%), phenol formaldehyde resin (3.1%), 4-tert-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Stress has been repeatedly documented to play a decisive role in the pathogenesis of alopecia areata [30], as well as in a variety of other skin diseases [31]. We have recently shown that acute immobilization stress led to activation of rodent skin mast cells [16].…”
Section: Discussionmentioning
confidence: 99%
“…Stress has been repeatedly documented to play a decisive role in the pathogenesis of alopecia areata [30], as well as in a variety of other skin diseases [31]. We have recently shown that acute immobilization stress led to activation of rodent skin mast cells [16].…”
Section: Discussionmentioning
confidence: 99%
“…Muller and Winkelmann [57]observed an association between acute emotional stress and illness onset only in 12% of their large sample of 736 patients. Gupta et al [58]studied 44 patients, of whom 13 had alopecia areata, 3 had alopecia totalis and 28 had alopecia universalis, reporting that 16% believed that stress played an important role in the onset or in the exacerbation of their disease. They also investigated the relationship between life events in the preceding 6 months as measured with the Social Readjustment Rating Scale and the severity of alopecia; they found that more severely affected patients did not differ from less severely affected patients with respect both to the number of life events and subjective rating of distress.…”
Section: Alopecia Areatamentioning
confidence: 99%
“…In the first patch test session, diglycidyl ether of bisphenol A (DGEBA,1% pet) provoked a weak (?+) reaction in a modified European standard series, and brominated epoxy resin (ER) a 2+ reaction. Plastics and glues [1]except ER compounds, and a series of antimicrobials were negative. The patient was tested with 15 of his ‘own’ compounds used at work, and 13 of them provoked an allergic patch test reaction (fig.…”
Section: Case Reportmentioning
confidence: 99%
“…Epoxies and plastics are well known causes of occupational allergic contact dermatitis [1, 2, 3, 4]. The plastic composite product industry is diverse, and a great variety of processing methods and materials are used.…”
Section: Introductionmentioning
confidence: 99%